The Baetic-Rifan firs (Abies pinsapo and Abies marocana): geospatial reference data for comparative analysis and conservation of the westernmost circum-Mediterranean firs. - Gutiérrez Hernández, Oliver (My University, 2025)
The Baetic–Rifan firs, represented by Abies pinsapo Boiss., endemic to southern Spain, and Abies marocana Trab., endemic to northern Morocco, define the south-western limit of the circum-Mediterranean fir group, with the Strait of Gibraltar separating their ranges. Both species are relict, highly restricted in distribution, and classified as Endangered on the IUCN Red List, facing pressures from habitat fragmentation and the compounded effects of climate change, particularly prolonged drought and heightened wildfire risk. Despite their ecological and phylogenetic affinity, they have rarely been addressed in a unified biogeographical framework, which is crucial to strengthen comparative analysis and transboundary conservation strategies under the Intercontinental Biosphere Reserve of the Mediterranean. This research presents a harmonised geospatial reference database that integrates current distribution data of A. pinsapo and A. marocana. For A. pinsapo, baseline data from the Andalusian Environmental Information Network were used. In contrast, the mapping of A. marocana was conducted using multiple sources, photo-interpretation of high-resolution imagery, and ancillary variables such as tree cover and canopy height. A unified legend was applied to classify the Baetic–Rifan fir forests into four categories: pure stands, mixed dominant stands, mixed secondary stands, and scattered occurrences. The results provide the first consistent comparison of forest cover across the Baetic–Rifan system. A. pinsapo currently occupies 2,690 hectares, including 918.99 ha of pure stands, 407.02 ha of mixed dominant stands, 414.88 ha of mixed secondary stands, and 949.81 ha of scattered occurrences. In contrast, A. marocana covers 4,206 hectares, with 1,648.25 ha of pure stands, 802.40 ha of mixed dominant stands, 1,385.26 ha of mixed secondary stands, and 370.96 ha of scattered occurrences.
The Baetic-Rifan firs (Abies pinsapo and Abies marocana)
Keywords: Abetos - Mediterráneo (Región); Fitogeografía; Abies pinsapo; Abies marocana; Spanish fir; Moroccan fir; Intercontinental Biosphere Reserve of the Mediterranean; Talassemtane National Park; Sierra de las Nieves National Park; Circum-Mediterranean firs